Olympic Programme Commission - Programme Review (2013)
In November 2002, at the Session in Mexico City, the IOC decided to systematically review the composition of the sports programme after each edition of the Olympic Games to ensure that its composition continues to be relevant and meet the expectations of future sporting generations. It was also decided to curb the growth of the Olympic programme, thus limiting the number of sports to 28 and the number of athletes to 10,500.